Pathogenic microorganism DNA high-throughput genetic sequencing to diagnose peritoneal dialysis-associated peritonitis due to Mycobacterium tuberculosis infection - Rui-feng Xu; Wu-niri Gao; Ta-la Hu; Xi-feng Wang; Jian-rong Zhao; Yan Meng (BMC Nephrology, 2024)
Abstract Peritoneal dialysis-associated peritonitis is a serious complication of peritoneal dialysis, and the prevention and treatment of this condition are important for improving the long-term survival and quality of life of patients. However, peritoneal dialysis-associated peritonitis due to Mycobacterium tuberculosis infection is relatively rare and not easily diagnosed. Here, we present a case of peritoneal dialysis-associated peritonitis caused by Mycobacterium tuberculosis identified by pathogenic microbial DNA high-throughput genetic sequencing. This case demonstrates that pathogenic microbial DNA high-throughput genetic sequencing could be used to improve the detection rate of pathogenic microorganisms in patients with complex conditions, thereby allowing for earlier initiation of treatment.